Bile micelle binding of structurally diverse ionized drug molecules - Mayu Konishi; Kiyohiko Sugano (ADMET and DMPK, 2025)
Background and purpose: Predicting the food effect on oral drug absorption by physiologically based biopharmaceutical modelling (PBBM) remains challenging. The bile micelle unbound fraction (fu) is one of the primary determinants of the negative food effect for high solubility drugs. To calculate the pH-fu profile for PBBM, the bile micelle partition coefficients of ionized and un-ionized drug species (Kbm,z, z: charge) are required. The general rules for the ratio of the partition coefficients of ionized and un-ionized drug species have been reported for the octanol/water (Poct) and phosphatidylcholine liposome/water partition coefficients. However, the general rule for the bile micelle partition coefficient has not yet been investigated. The purpose of the present study was to clarify the general rule for Kbm,z≠0/Kbm,0. Experimental approach: The pH-fu profiles of 4 monovalent weak acids, 8 monovalent weak bases, 2 divalent weak bases, and 2 zwitterion drugs were measured by dynamic dialysis in the pH range about pKa ± 2. Bile micelles consisted of taurocholic acid (TC)/egg lecithin (15 mM/ 3.75 mM). Kbm,z was calculated from the pH-fu profiles. Key results: Kbm,-1/Kbm,0 was ≤ 0.03 for all monovalent acids. Kbm,+1/Kbm,0 ranged from 0.24 to 2.6. Kbm,+2/Kbm,0 was about 0.3. For the two zwitterionic drugs, Kbm,-1/Kbm,±0 was 1.1 and 2.3, and Kbm,+1/Kbm,±0 was 3.9 and 20, respectively. Kbm,0 roughly correlated with Poct (r = 0.68). Conclusion: The bile micelle binding of anionic drug species (z = -1) is generally negligible, whereas that of cationic drug species (z = +1) can be significant. A general rule for Kbm,+1/Kbm,0 was not found. Kbm,+1/Kbm,0 can be greater than 1 in several cases, suggesting an attractive electrostatic interaction between the positive charge of a drug and the negative charge of TC. These points should be considered in food effect prediction.